SLACK RESOURCES, FEMINISME DEWAN, DAN KUALITAS PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Anggraeni, Dian Yuni; Djakman, Chaerul D. (UI Scholars Hub, 2017)
The objective of this study is to examine the impact of slack resources and board’s feminism on CSR disclosure quality. This study also investigates the role of board’s feminism in moderating the relationship between slack resources and CSR disclosure quality. The analysis of this study uses moderated regression analysis with unbalanced panel data. The sample consists of 114 firms-years which are listed in IDX and reported sustainability report for 2012-2014. The results find that slack resources have positive impact on CSR disclosure quality, while the feminism on board of commissioners have negative effect on CSR disclosure quality. There is no relationship between director’s feminism and CSR disclosure quality. The result also shows that feminism on directors and commissioners does not moderate the relationship between slack resources and CSR disclosure quality. This is probably because the boards in Indonesian public companies are still dominated by men.